Strategies Towards Antigen-Specific Treatments for Membranous Nephropathy - Köllner, Sarah M. S.; Seifert, Larissa; Zahner, Gunther; Tomas, Nicola M. (Frontiers in Immunology, 2022)
Membranous nephropathy (MN) is a rare but potentially severe autoimmune disease and a major cause of nephrotic syndrome in adults. Traditional treatments for patients with MN in-clude steroids with alkylating agents such as cyclophosphamide or calcineurin inhibitors such as cyclosporine, which have an undesirable side effect profile. Newer therapies like rituximab, although superior to cyclosporine in maintaining disease remission, do not only affect patho-genic B or plasma cells, but also inhibit the production of protective antibodies and therefore the ability to fend off foreign organisms and to respond to vaccination. These are undesired effects of general B or plasma cell-targeted treatments. The discovery of several autoanti-gens in patients with MN offers the great opportunity for more specific treatment approaches. Indeed, such treatments were recently developed for other autoimmune diseases and tested in different preclinical models, and some are about to jump to clinical practice. As such treat-ments have enormous potential to enhance specificity, efficacy and compatibility also for MN, we will discuss two promising strategies in this perspective: The elimination of pathogenic an-tibodies through endogenous degradation systems and the depletion of pathogenic B cells through chimeric autoantibody receptor T cells.